DETERMINANTS AND MOTIVES FOR APPLYING STRATEGIC MANAGEMENT ACCOUNTING TECHNIQUES IN THE PUBLIC SECTOR: THEORETICAL STUDY (World Bulletin of Management and Law, 2023)
The study aimed to identify the determinants and motives for applying modern strategic management accounting techniques in the public sector on the same approach used in the private sector. The study dealt with the basic concepts of the techniques that were applied in the public sector entities, such as the balanced scorecard technique, the activity-based costing technique, the quality costing technique, and measuring the cost of service provided by the public sector entities. My theory is supported by a group of Arab and foreign researches that dealt with strategic management accounting techniques. The study concluded that there are many determinants that impede the application of strategic management accounting techniques in the public sector, the most prominent of which is the political determinants, since the public sector entities are wholly subordinate to the government. So they are bound by the provisions and legislation of the state, and therefore their management is not financially and administratively independent, in addition to the unwillingness shown by them. Most of the employees and workers in those entities, when talking about change, depart from the traditional systems that are applied in those entities, and in return, the process of applying and implementing technologies will lead to measuring, analyzing and evaluating performance in a fair and accurate manner and providing information that contributes to rational decision-making
Keywords: Strategic management; public sector; decision-making; accounting techniques